2010
DOI: 10.1016/j.jplph.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously applied isothiocyanates enhance glutathione S-transferase expression in Arabidopsis but act as herbicides at higher concentrations

Abstract: Isothiocyanates (ITCs) are sulfur-containing compounds that are generated by the glucosinolate-myrosinase system in plants. Although previous greenhouse studies have demonstrated the phytotoxicity of ITCs, their action modes are still unknown. In this study, we report the physiological responses of Arabidopsis thaliana treated with three exogenous ITCs: methyl ITC, allyl ITC, and phenethyl ITC. Administration of a high dose of each ITC inhibited plant growth and induced severe bleaching in the rosette leaves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 44 publications
11
54
0
Order By: Relevance
“…Recently, it has been demonstrated that the exogenous addition of two isothiocyanates, phenethyl- and allyl-isothiocyanates, enhanced heat tolerance in Arabidopsis plants by increasing the expression level of heat shock proteins and H 2 O 2 accumulation [85,86]. It was determined that the mode of action of phenethyl-isothiocyanate (PEITC) was similar to salicylic acid (SA), a heat tolerance inducer that inhibits the catalase activity in plants and produces the H 2 O 2 accumulation [87], but the molecular mechanisms behind the recognition of both compounds may be different and worth study.…”
Section: Changes In the Glucosinolate Profile Under Abiotic Stressmentioning
confidence: 99%
“…Recently, it has been demonstrated that the exogenous addition of two isothiocyanates, phenethyl- and allyl-isothiocyanates, enhanced heat tolerance in Arabidopsis plants by increasing the expression level of heat shock proteins and H 2 O 2 accumulation [85,86]. It was determined that the mode of action of phenethyl-isothiocyanate (PEITC) was similar to salicylic acid (SA), a heat tolerance inducer that inhibits the catalase activity in plants and produces the H 2 O 2 accumulation [87], but the molecular mechanisms behind the recognition of both compounds may be different and worth study.…”
Section: Changes In the Glucosinolate Profile Under Abiotic Stressmentioning
confidence: 99%
“…Recently, we reported that ITCs showed herbicidal effects when applied to Arabidopsis at high doses (Hara et al 2010). Before demonstrating the herbicidal effects of ITCs at the field scale, we first attempted to confirm the ITCs' effects on Arabidopsis in the greenhouse.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that AITC induced stomatal closure in Arabidopsis accompanied by ROS and NO production as second messengers. At higher than 1 m m , AITC shows cytotoxicity on Arabidopsis (Hara et al . 2010), whereas even 10 µ M AITC significantly induced stomatal closure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…So far, Zhao et al . (2008) reported that glucosinolate‐myrosinase system enhances ABA‐inhibition of guard cell inward K + channels and of stomatal opening and Hara et al . (2010) reported that application of exogenous ITCs including AITC is harmful at the higher dosage while at lower concentration enhances glutathione S ‐transferase (GST) activity in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%